92O Nivolumab plus low-dose ipilimumab as first-line treatment of advanced NSCLC: Overall survival analysis of checkmate 817. (15th December 2019) - Barlesi, F; Audigier-Valette, C; Felip, E; Ciuleanu, T-E; Jao, K; Rijavec, E; Urban, L; Aucoin, J-S; Zannori, C; Vermaelen, K; Frontera, O Arén; Ready, N; et al.
Abstract: Background: Nivolumab (NIVO) + ipilimumab (IPI) combination demonstrated improved overall survival (OS) benefits vs chemotherapy as first-line treatment for advanced NSCLC in both tumor programmed death ligand 1 (PD-L1) expression ≥ 1% and < 1% in CheckMate 227. CheckMate 817 is a multi-cohort, single arm, phase IIIb study evaluating the safety of flat-dose NIVO + weight-based low-dose IPI in advanced NSCLC. Preliminary safety and efficacy results were previously reported for cohorts A and A1. Here we present additional safety data and OS in these cohorts. Methods: Patients with previously untreated stage IV or recurrent NSCLC, and no known sensitizing EGFR or ALK alterations, were eligible regardless of PD-L1 expression. Cohort A (n = 391) had ECOG performance status (PS) 0–1; cohort A1 (special populations; n = 198) had ECOG PS 2 or a specified comorbidity (asymptomatic untreated brain metastases, hepatic or renal impairment, or HIV). Patients were treated with NIVO 240 mg Q2W + low-dose IPI 1 mg/kg Q6W for 2 years or until disease progression/unacceptable toxicity. Safety in cohort A was the primary endpoint; efficacy endpoints were secondary/exploratory; A1 safety and efficacy analyses were exploratory. Results: Baseline characteristics apart from ECOG PS and comorbidities were similar between cohorts. With minimum follow-up of 21 months (A) and 14 months (A1), median OS was 17.0 months and 9.9 months, respectively. At 1 year, 60% of patients in A and 47% of patients in A1 were alive. OS by PD-L1 expression and tumor mutational burden levels will be presented. The safety profile (type and rate of treatment-related adverse events [TRAEs]) was consistent between the cohorts. The range of median time to onset of select TRAEs was similar between cohorts A (2–26 weeks) and A1 (2–21 weeks). The majority of select TRAEs have resolved (40%–100%). Conclusion: Select TRAE profile of NIVO + low-dose IPI was similar between cohorts A and A1. Durable OS outcomes were observed with first-line NIVO+IPI in patients with advanced NSCLC (cohort A) and were comparable to CheckMate 227; although as expected, comorbidities and/or poor performance status impacted outcomes in cohort A1. Clinical trial identification: NCT02869789. Editorial acknowledgement: Writing and editorial assistance was provided by Mhairi Laird, PhD, of Caudex and funded by Bristol-Myers Squibb. Legal entity responsible for the study: Bristol-Myers Squibb. Funding: Bristol-Myers Squibb. Disclosure: F. Barlesi: Honoraria (self): AstraZeneca, Bayer, Bristol-Myers Squibb, Boehringer Ingelheim, Eli Lilly Oncology, F. Hoffmann–La Roche Ltd, Novartis, Merck, MSD, Pierre Fabre, Pfizer, Takeda; Advisory / Consultancy: AstraZeneca, Bayer, Bristol-Myers Squibb, Boehringer Ingelheim, Eli Lilly Oncology, F. Hoffmann–La Roche Ltd, Novartis, Merck, MSD, Pierre Fabre, Pfizer, Takeda; Research grant / Funding (institution): AbbVie, ACEA, Amgen, AstraZeneca, Bayer, Bristol-Myers Squibb, Boehringer Ingelheim, Eisai, Eli Lilly Oncology, F. Hoffmann–La Roche Ltd, Genentech, Ipsen, Ignyta, Innate Pharma, Loxo, Novartis, Medimmune, Merck, MSD, Pierre Fabre, Pfizer, Sanofi-Aventis, ; Non-remunerated activity/ies: Principal Investigator for AstraZeneca, Bristol-Myers Squibb, Merck, Pierre Fabre and Roche sponsored trials (or ISR). C. Audigier-Valette: Honoraria (self): AbbVie, Pfizer; Honoraria (institution): Roche, MSD, Bristol-Myers Squibb, AstraZeneca; Advisory / Consultancy: Roche, MSD, Bristol-Myers Squibb, AstraZeneca, AbbVie, Pfizer. E. Felip: Advisory / Consultancy: AbbVie, AstraZeneca, Blue Print Medicines, Boehringer Ingelheim, Bristol-Myers Squibb, Celgene, Eli Lilly, Guardant Health, Janssen, Medscape, Merck KGaA, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Takeda, TouchTime; Speaker Bureau / Expert testimony: AbbVie, AstraZeneca, Boehringer Ingelheim, Bristol-Myers Squibb, Eli Lilly, Merck KGaA, Merck Sharp & Dohme, Novartis, Pfizer, Roche, Takeda. T-E. Ciuleanu: Advisory / Consultancy: Astellas, Janssen, Bristol-Myers Squibb, Merck Serono, Amgen, Roche, Pfizer, Boehringer Ingelheim, Lilly, AstraZeneca, MSD, Sanofi, Novartis, Servier, AD Pharma. K. Jao: Advisory / Consultancy: AbbVie, AstraZeneca, Bayer, Bristol-Myers Squibb, Pfizer, Merck, Takeda, Roche; Speaker Bureau / Expert testimony: AstraZeneca/CIOSK. J-S. Aucoin: Advisory / Consultancy: AstraZeneca, Bristol-Myers Squibb, Merck, Novartis, Pfizer, Roche; Speaker Bureau / Expert testimony: AstraZeneca, Merck, Pfizer, Roche. K. Vermaelen: Honoraria (self): MSD, Roche; Honoraria (institution): Bristol-Myers Squibb; Advisory / Consultancy: MSD, Bristol-Myers Squibb, Roche; Research grant / Funding (institution): Bristol-Myers Squibb. O. Arén Frontera: Full / Part-time employment: Pfizer. N. Ready: Honoraria (self): Bristol-Myers Squibb, AstraZeneca, G1 therapeutics, Merck, Genentech, AbbVie, Bristol-Myers Squibb – unbranded speaker, Celgene – unbranded speaker; Advisory / Consultancy: Bristol-Myers Squibb, AstraZeneca, G1 therapeutics, Merck, Genentech, AbbVie; Speaker Bureau / Expert testimony: Bristol-Myers Squibb – unbranded speaker, Celgene – unbranded speaker; Research grant / Funding (self): Merck investigator-initiated trial. A. Curioni: Advisory / Consultancy: AstraZeneca, Bristol-Myers Squibb, Boehringer Ingelheim, MSD, Roche, Pfizer, Takeda. H. Linardou: Advisory / Consultancy: Bristol-Myers Squibb, MSD, AstraZeneca, Roche; Speaker Bureau / Expert testimony: AstraZeneca. R. Pillai: Research grant / Funding (self): Bristol-Myers Squibb. S. Li: Full / Part-time employment: Bristol-Myers Squibb. A. Acevedo: Shareholder / Stockholder / Stock options: Bristol-Myers Squibb; Full / Part-time employment: Bristol-Myers Squibb. L. Paz-Ares: Honoraria (self): Roche, MSD, Lilly, Novartis, Boehringer Ingelheim, AstraZeneca, Amgen, Sanofi, Pharmamar, Pfizer, Bristol-Myers Squibb, Merck, Takeda, Celgene, Servier, Sysmex, Incyte, Ipsen, Adacap, Bayer, Blueprint; Leadership role: Altum Sequencing; Research grant / Funding (institution): MSD, AstraZeneca, Pfizer, Bristol-Myers Squibb. All other authors have declared no conflicts of interest.